Strength and conditioning training for track athletes
Strength training is an essential part of training for the middle distances. If done intelligently, it can provide an athlete with a body that is stronger and more capable of withstanding the overload that a systematic multi-paced training program requires. On the other hand, if it is not done correctly or with a specific purpose in mind, you could end up with undesirable physical results and lot of wasted training time. That's why author describes the basics of strength training (not only weight training!) for the middle distance runner (weighttraining, stretching, plyometrics).